Lymphadenopathy as a manifestation of amyloidosis: a case series. (December 2014) - Fu, Julie; Seldin, David C.; Berk, John L.; Sun, Fangui; O'Hara, Carl; Cui, Haili; Sanchorawala, Vaishali
Abstract Lymphadenopathy as a manifestation of amyloidosis is rare. Of 3008 new patients with amyloidosis evaluated from 1994 to 2013 at a single center, 47 (1.6%) presented with lymph node enlargement leading to a biopsy and the diagnosis. We conducted a retrospective review of the initial presentation, time to progression, and treatment outcomes for these patients. Upon initial evaluation, 14 (30%) had isolated lymphadenopathy while 33 (70%) had evidence of vital organ involvement. Thirty-nine patients (83%) had systemic AL amyloidosis at initial evaluation or developed it on follow up; there was a single case each of AA, wtTTR and V122ITTR and one untyped amyloidosis. Eleven patients (23%) had IgM monoclonal gammopathy and 3 (6%) had histology consistent with lymphoplasmacytic lymphoma. Of the 14 patients with isolated lymphadenopathy, 10 (71%) eventually progressed to other organ disease requiring treatment at a median time of 10 months (range 4–71). This series demonstrates that patients presenting with amyloid lymphadenopathy usually have AL amyloidosis, and should have a thorough evaluation for other organ involvement at diagnosis. If present, treatment should be similar to that of other patients with systemic AL amyloidosis, but if not, patients should be monitored regularly for development of other organ disease over time.